Artificial Intelligence in Medical Education: Balancing Emerging Opportunities with Real-World Limitations - Kubba, Ali; Khunda, Aethele; Al-Ameri, Laith; Hameed, Ekhlas Khalid (AL-Kindy College Medical Journal, 2025)
The integration of Artificial Intelligence into medical education is a newly emerging and promising strategy that transforms the outlook of the learning process. This continuously evolving technology influences various aspects of medical education, including curriculum design, learning, and assessment. This editorial will discuss how AI is reshaping all aspects of medical education, highlighting challenges and issues, including bias, data governance, and excessive dependence on technology that may be encountered.